PAKOM PETERNAK PUYUH DESA GAJAHAN COLOMADU KARANGANYAR - Lukman Hakim; Dedi Hanwar; Eko Sugiyanto; Zulfa Irawati (WARTA LPM, 2015)
The purpose of this activity is improving knowledge and skill of quail farmer’s in waste management of quail. The management of waste is processing of organic fertilizer. The participate in the activity are quail farmer’s in RW II Sub-village Ginung, Gajahan Village, Colomadu, Karanganyar. The result of this activity in step I that is be good attention from a quail farmer’s especiality at trainning time process of product organic fertilizer. As for its result as follows; trainning and assistence quail farmer’s is followed enthusiastic fully by participant and greeted positive by head of Village Gajahan Colomadu, Karanganyar. That are many question in trainning process of product organic fertilizer. The others result in activity is a quail farmer’s started processing of product organic fertilizer in housebreed themselves. The  processing of product organic fertilizer will be clean in Gajahan Village environment and also this activity will be value added toward income quail farmer’s.